MENGARAHKAN KETIDAKPUASAN KERJA PADA KINERJA KREATIF DALAM USAHA MEMBANGUN ORGANISASI YANG INOVATIF DALAM PERSPEKTIF INTERAKSIONIS - Wikaningrum, Tri (Fokus Ekonomi, 2006)
This article focused on creativity as an expression of voice and on the specific conditions that may result in dissatisfaction being channeled into creative performance. By creating an appropriate context, organizations can encourage employees who experience job dissatisfaction to engage in creative activities. Integrating the exit-voice theory and the organizational creativity theory, there are three contextual variables: feedback from coworkers, coworker helping and support, and perceived organizational support for creativity. The starting point for our theoretical development is provided by the interactionist perspective of creative behavior developed by Woodman and Schoenfeldt (1989). This model captures the dynamic, interactive nature of persons and situations across multiple levels of social organization.Keywords:       Creativity, Dissatisfaction, Exit-Voice Theory, Interactionist Perspective